A Framework for estimating piping reliability subject to corrosion under insulation - Mokhtar, A.A. (EDP Sciences, 2014)
Corrosion under insulation (CUI) is one of the serious damage mechanisms experienced by insulated piping systems. Optimizing the inspection schedule for insulated piping systems is a major challenge faced by inspection and corrosion engineers since CUI takes place beneath the insulation which makes the detection and prediction of the damage mechanism harder. In recent years, risk-based inspection (RBI) approach has been adopted to optimize CUI inspection plan. RBI approach is based on risk, a product of the likelihood of a failure and the consequence of such failure. The likelihood analysis usually follows either the qualitative or the semi-qualitative methods, thus precluding it to be used for quantitative risk assessment. This paper presents a framework for estimating quantitatively the likelihood of failure due to CUI based on the type of data available. Â© 2014 Owned by the authors, published by EDP Sciences.